2003
DOI: 10.1108/02621710310495775
|View full text |Cite
|
Sign up to set email alerts
|

Executive education programs go back to school

Abstract: Executive education (EE) programs are an important part of many business schools' mission. For many such providers, the 1990s was a robust time of growth and increased reliance on the fruits of those programs. In less time than takes to build a new EE facility, the EE environment changed. What factors influence the desirability of an EE program experience for the executives who attend them? Do executives want more EE opportunities or less? Are online program offerings an attractive alternative to traditional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 1 publication
0
13
0
1
Order By: Relevance
“…Conger and Xin (2000, p. 73), for example, characterized this group as those who seek to " . Because they are in a learning environment alongside their corporate peers, these participants appreciate the value of learning not only from the instructor (Conger & Xin, 2000;Farris, Haskins, & Yemen, 2003) but from each other (Mento & Larson, 2004). .…”
Section: Executive Education Audiencesmentioning
confidence: 99%
See 3 more Smart Citations
“…Conger and Xin (2000, p. 73), for example, characterized this group as those who seek to " . Because they are in a learning environment alongside their corporate peers, these participants appreciate the value of learning not only from the instructor (Conger & Xin, 2000;Farris, Haskins, & Yemen, 2003) but from each other (Mento & Larson, 2004). .…”
Section: Executive Education Audiencesmentioning
confidence: 99%
“…For example, Farris et al (2003) identified a demand for finance-related expertise in executive education (e.g., mergers and acquisitions, derivatives, and project finance) that could well have both functional and strategic components. For example, Farris et al (2003) identified a demand for finance-related expertise in executive education (e.g., mergers and acquisitions, derivatives, and project finance) that could well have both functional and strategic components.…”
Section: Concluding Thoughtsmentioning
confidence: 99%
See 2 more Smart Citations
“…The motivating reasons why executives enrol in these programmes include: personal development and personal ambition, continuous professional development and industry specialisation, a pathway to promotion or a platform for career change, and enhancing their understanding of company strategic challenges (Farris, Haskins, & Yemen, 2003 Being able to bridge the 'corporate education security gap' is another key reason for companies and their employees to enrol in executive education programmes (Goodwin & Fulmer, 1995, p. 10). it is apparent that executive education programmes, need to be market driven and be able to satisfy the needs and expectations of programme participants (Farris, Haskins, & Yemen, 2003) amongst other key stakeholders. While the focus of executive education programmes has evolved away from its traditional role of providing general or functional knowledge to its newer role as a level for orchestrating organisational change, the challenge for those designing the programmes has also increased significantly.…”
Section: Introductionmentioning
confidence: 99%